PENGARUH TEMPERATUR TUANG TERHADAP POROSITAS, STUKTUR MIKRO DAN KEKERASAN DARI ALUMUNIUM RONGSOK VELG MENGGUNAKAN PENGECORAN EVAPORATIF - Putra, Fajar Perdana; siswanto, rudi (Universitas Lambung Mangkurat, 2021)
The second largest metal material used after steel is Aluminum and its alloys. Ranging from aircraft bodies, vehicles, engine components, ship components, to buildings and very diverse applications using aluminum alloys. Material for making alloy wheels for components in motors using one of the special aluminum alloy applications with regard to the strength and hardness of high-quality aluminum alloys. Industrial companies that make aluminum doors, including windows and frames, make aluminum shelves, storefronts and other products. Produce waste remnants of used aluminum which can be used as aluminum as the main material destination. To reduce the company's production costs, many of them use aluminium scrap as their main casting material. Casting uses a temperature of 650 ° C, 700 ° C, 750 ° C, 800 ° C including casting type evaporative or casting using Styrofoam. The missing styrofoam casting pattern is a casting that uses a pattern of material that can evaporate when exposed to molten metal heat. The casting temperature results can affect microstructure, hardness, porosity and structure.